Nevus Lipomatosus Cutaneous Superficialis of Hoffmann and Zurhelle: a rare cutaneous hamartoma - KC, S.; Aryal, A.; Jha, A.; Karn, D. (Kathmandu University Medical Journal, 2022)
Nevus lipomatosus cutaneous superficialis (NLCS) is a rare idiopathic cutaneous hamartoma characterized by ectopic clusters of mature adipose tissues in dermis. It is classified into two types. Classical type presenting as multiple lesions with onset at birth or within third decade of life and solitary type with onset between third to sixth decade of life. Here we present a case of 45 years female with adult onset, asymptomatic, grouped, skin colored, soft sessile growth in zosteriform pattern on left buttock. We here intend to report rare case of classical Nevus Lipomatosus Cutaneous Superficialis.